Vehicle parking standards as a support to sustainable transport system: Belgrade case study - Milosavljevic, Nada; Simicevic, Jelena; Maletic, Goran (Technological and Economic Development of Economy, 2010)
Vehicle parking standards are related exclusively to parking in connection with: planning, construction, development and/or extension and change of use of the existing developments. On the other hand, vehicle parking standards are the key measure for managing the level of traffic and they should be an integral part of the urban transport policy. This would allow the parking standards to be applied also to the land use management in accordance with accessibility to the urban zones by means of travel other than by car. This implies that in the course of producing vehicle parking standards the level of parking restrictions is to be defined depending on the Public Transport Accessibility Level. If Public Transport Accessibility Level of a zone the subject development belongs to is high, the number of parking spaces to be provided is restricted and customers are encouraged to shift to alternative transport modes. Thus defined parking standards assist in the development of sustainable transport system. This paper will present the methodology for calculation of parking standards depending on the accessibility of the zone the subject development is located within. Article in English. Automobilių aikštelių standartai kaip darnios transporto sistemos palaikymo priemonė: Belgrado atvejis Santrauka. Transporto priemonių stovėjimo vietų standartai numato naujų automobilių aikštelių planavimą ir statybą, esamų statinių išplėtimą ar pakeitimą. Kita vertus, automobilių aikštelių standartai yra pagrindinė priemonė, padedanti valdyti transporto srauto lygi. Jie tūretų būti neatsiejami nuo miesto transporto politikos. Tai leistų įvairias miesto zonas vykti ne automobiliais. Tai reiškia, kad automobilių aikštelių apribojimai turi būti suderinti su miesto viešojo transporto sistema. Jei viešojo transporto prieinamumo lygis konkrečioje miesto zonoje yra aukštas, automobiliu aikšteliu skaičius turi būti ribojamas, o miestiečiai turi būti skatinami naudotis alternatyviomis transporto rūšimis. Taip automobilių aikštelių standartai padeda pletoti darnia transporto sistema. Šiame straipsnyje pateikiama automobilių aikštelių skaičiavimo metodologija, įvertinanti atskirų miesto zonų pasiekiamumą. Reikšminiai žodžiai: automobilių aikštelių standartas, viešojo transporto prieinamumo lygis, patrauklumo lygis, darni transporto sistema, žemenauda, Belgradas. First published online: 10 Feb 2010